Anemia, sex, and race as predictors of morbidity or mortality after knee arthroplasty surgery. Issue 12 (5th October 2020) - Mazzeffi, Michael; Taneja, Monica; Porter, Steven; Chow, Jonathan H.; Jackson, Bryon; Fontaine, Magali; Frank, Steven M.; Tanaka, Kenichi
Abstract: Background: Anemia is associated with poor outcome after major joint replacement surgery, but it is unclear whether sex and race modify its impact on outcome. We hypothesized that anemia would be associated with increased morbidity or mortality after knee arthroplasty surgery and that sex and race would be effect modifiers for this relationship. Study Design and Methods: We performed a retrospective cohort study of elective knee arthroplasty patients between 2013 and 2018 using data from the National Surgical Quality Improvement Program. Morbidity or mortality after surgery was compared between patients without anemia, with mild anemia, and with moderate to severe anemia. Multivariable logistic regression was used to determine adjusted odds for morbidity or mortality with anemia. Interaction terms were entered into the model to test for effect modification by sex and race. Results: 243 491 patients were included and 30 135 patients (12.4%) were anemic. Morbidity or mortality occurred in 3.7% of patients without anemia, 5.2% of patients with mild anemia, and 7.1% of patients with moderate to severe anemia ( P < .001). After adjustment for confounding variables, mild anemia OR = 1.36 (95% CI = 1.28‐1.45), and moderate to severe anemia OR = 1.92 (95% CI = 1.72‐2.13) were associated with increased odds of morbidity or mortality. Sex, but not race, was a significant effect modifier with men having a greater increase in morbidity or mortality when anemic ( P = .02). Conclusions: Anemia is associated with increased morbidity or mortality after knee arthroplasty surgery and men have a greater increase in perioperative risk than women when anemic.